COMPREHENSIVE MIDWIFERY CARE FOR A PRIMIGRAVIDA WITH BACK PAIN - Oktri, Yosi; Nuryani, Yanyan; Neng Suaidah; Astuti, Widya Putri (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2024)
During the third trimester of pregnancy, a woman will usually experience changes that will cause a lot of discomfort, one of which is back pain. This complaint can be overcome with non-pharmacological treatment, one of which is endorphin massage. Based on data at PMB "N" in 2023, out of 82 third trimester pregnant women, 73.58% experienced back pain discomfort. This study aims to determine midwifery care to reduce the intensity of back pain in third trimester pregnant women. Data collection methods with interviews, observations, and documentation studies. The subject of this midwifery care is Mrs. "A" G1P0A0 37 weeks gestation with complaints of back pain discomfort. The results showed that the comprehensive midwifery care carried out took place normally without any complication. During pregnancy, Mrs. "A" experienced back pain discomfort in the third trimester and was given endorphin massage care to relieve back pain. After the intervention was carried out 5 times, namely with the frequency of endorphin massage starting on the first day of the visit to the PMB and carried out again on day 3, day 5, day 6 and day 7 after the visit to the PMB, the back pain in Mrs. "A" decreased and she said she felt comfortable and more relaxed. It can be concluded comprehensive midwifery care in Mrs. "A" runs normally and effectively to overcome the discomfort experienced. This comprehensive midwifery care is expected to be applied to minimize complications that may occur during pregnancy, childbirth, newborn, postpartum to contraceptive services. Keywords: Back Pain, Endorphin Massage, Use of Video